1985
DOI: 10.1002/cne.902390209
|View full text |Cite
|
Sign up to set email alerts
|

Development of the trochlear nucleus in quail and comparative study of the trochlear nucleus, nerve, and innervation of the superior oblique muscle in quail, chick, and duck

Abstract: The present study was undertaken to examine the development of the trochlear nucleus in quail and to compare the mature trochlear nucleus, nerve, and their sole target of innervation, the superior oblique muscle, in quail, chick, and duck. Study of the trochlear nucleus in quail from embryonic day 5 through hatching shows a maximum of 1,248 neurons on embryonic day 10 followed by spontaneous degeneration of 40% of the neurons between days 10 and 16. Previous studies have shown that although the initial and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Trochlear motor neurons develop both within and posterior to the isthmic organiser Previous studies variously reported the location of trochlear motor neuron cell bodies as being within the midbrain, isthmus or within rhombomere 1 (r1) of the hindbrain (Altman and Bayer, 1981;Bubien-Waluszewska, 1981;Lumsden, 1990;Lumsden and Keynes, 1989;Sohal et al, 1985). Fgf8 is expressed at the isthmus and can reproduce all of its patterning activities thereby providing the most useful marker for the isthmic organiser.…”
Section: Resultsmentioning
confidence: 99%
“…Trochlear motor neurons develop both within and posterior to the isthmic organiser Previous studies variously reported the location of trochlear motor neuron cell bodies as being within the midbrain, isthmus or within rhombomere 1 (r1) of the hindbrain (Altman and Bayer, 1981;Bubien-Waluszewska, 1981;Lumsden, 1990;Lumsden and Keynes, 1989;Sohal et al, 1985). Fgf8 is expressed at the isthmus and can reproduce all of its patterning activities thereby providing the most useful marker for the isthmic organiser.…”
Section: Resultsmentioning
confidence: 99%
“…The domestic duck has a long history of being included in avian chimeras as a way to study those patterning mechanisms that make embryos morphologically distinct (Waddington, 1930(Waddington, , 1932Hampe, 1957;Zwilling, 1959;Dhouailly, 1967Dhouailly, , 1970Pautou, 1968;Sohal, 1976;Sohal et al, 1985Sohal et al, , 1990Sohal, 1986, 1987). But the combination of Japanese quail (Coturnix coturnix japonica) and White Pekin duck (Anas platyrhynchos) as donors and/or hosts adds value for at least four reasons (Lwigale and Schneider, 2008).…”
Section: Quail-duck Chimerasmentioning
confidence: 99%
“…We focused much of our work on chicken, because the avian superior oblique muscle is easier to prepare into nerve-muscle preparations suitable for electrical stimulation and calcium imaging. Detailed information is available about muscle force, number of endplates, motor neurons, and myofibers in chicken EOMs of this age (Sohal et al, 1985; Hatton and von Bartheld, 1999; Croes and von Bartheld, 2005; Baryshnikova et al, 2007; Croes et al, 2007; Li et al, 2010, 2011). We describe two types of spontaneous and nerve-stimulation evoked calcium transients in avian EOMs, and we compare their physiological and pharmacological characteristics with the range of calcium transients previously reported in developing mammalian myotubes in culture (Flucher and Andrews, 1993; Jaimovich et al, 2000; Powell et al, 2001; Eltit et al, 2004; Campbell et al, 2006; Casas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%